Trehalose-Based Nucleolipids as Nanocarriers for Autophagy Modulation: An In Vitro Study - Anthony Cunha (Pharmaceutics, 2022)
The Autophagy Lysosomal Pathway is one of the most important mechanisms for removing dysfunctional cellular components. Increasing evidence suggests that alterations in this pathway play a pathogenic role in Parkinson’s disease, making it a point of particular vulnerability. Numerous studies have proposed nanotechnologies as a promising approach for delivering active substances within the central nervous system to treat and diagnose neurodegenerative diseases. In this context, the aim was to propose the development of a new pharmaceutical technology for the treatment of neurodegenerative diseases. We designed a trehalose-based nanosystem by combining both a small natural autophagy enhancer molecule named trehalose and an amphiphilic nucleolipid conjugate. To improve nucleolipid protection and cellular uptake, these conjugates were formulated by rapid mixing in either solid lipid nanoparticles (Ø = 120.4 ± 1.4 nm) or incorporated into poly(lactic-co-glycolic acid) nanoparticles (Ø = 167.2 ± 2.4 nm). In vitro biological assays demonstrated a safe and an efficient cellular uptake associated with autophagy induction. Overall, these nucleolipid-based formulations represent a promising new pharmaceutical tool to deliver trehalose and restore the autophagy impaired function.